Deformation and Stress Distribution of the Effective Water-Resisting Rock Beam under Water-Rock Coupling Action inside the Panel Floor - Baojie Fu; Hualei Zhang; Min Tu; Xiangyang Zhang (Advances in Civil Engineering)
The stability of panel floor, which is above confined water, is the key to determine the water inrush from the panel floor. Based on the characteristics of “lower three zones” of the panel floor, the mechanics analysis model of a floor water-resisting rock beam is established. Then, by the principle of virtual work and energy functional variational conditions, the trends of deflection and internal stress are researched in the effective water-resisting rock beam under the combined action of mining stress and water pressure. And how to determine its stability is acquired. According to the geological and mining conditions of A3 coal seam in Panxie mining area of Huainan Mining Group, three factors influencing on the stability of the floor rock beam are analyzed, such as elastic modulus, coefficient of viscosity, and water pressure. It is shown that the elastic modulus plays the most important role on the deformation of the rock beam. So, for improving the mechanical properties of the rock beam, the reinforcing floor technique has been proposed. On the one hand, it is contributed to improve the ability for resisting floor deformation. On the other hand, it can increase the coefficient of rock viscosity in water damage zones and reduce the speeds of loading and deformation in the whole rock beam. Hydrophobic decompression can effectively reduce the stress on the boundary of the rock beam, and the stability is enhanced. The research results have a guiding significance for determining whether there are water inrush risks in the panel above the confined aquifer.